Life Expectancy and SARS-CoV-2 Genomic Variations Plays Key Role in COVID-19 Transmission and Low Fatality Rate in Africa - Omotoso, Olabode (My University, 2020)
The novel coronavirus disease (COVID-19) has claimed lots of lives, posing a dire threat to public health and the global economy. The present study determined the severe acute respiratory syndrome-2 (SARS-CoV-2) genomic variability and the contributory factors to the observed low fatality rate in Africa. To assess the SARS-CoV-2 mutational landscape, 924 viral sequences from the Africa region with their sociobiological characteristics mined from the GISAID database were analyzed. The age of infected patients, the number of tests done, confirmed cases, recovery, fatality, and countries' age distribution were obtained to determine the age distribution, testing, recovery, and fatality rate. Mutational analysis of the SARS-CoV-2 sequences revealed highly recurrent mutations in the Spike glycoprotein D614G (97.2%), concurrent R203K, and G204R (65.2% respectively) in the N protein region, and P4715L (97.2%) in the RNA dependent RNA polymerase region. COVID-19 is more severe in older people (> 65 years), Africa has a low percentage of people within this age group (4.36%). The average age of the 924 infected patients in this study is 46 years with only 47 infected patients (5.1%) above 65 years in comparison to 13.12% in countries in other continents with the highest prevalence of COVID-19. Africa's young generation, the late incidence of the disease, and adherence to public health guidelines are important indicators that may have contributed to the observed low COVID-19 deaths in Africa. However, sufficient data is still unavailable due to low testing rate to ascertain the epidemiology, transmission, genomic variation, and the true impact of the pandemic in Africa
Keywords: Coronavirus; pandemic; mutations; low fatality; Africa; SARS-CoV-2; transmission; epidemiology; COVID-19; public health